A Guide to Transient Expression of Membrane Proteins in HEK-293 Cells for Functional Characterization - Ooi, Amanda; Wong, Aloysius; Esau, Luke; Lemtiri-Chlieh, Fouad; Gehring, Chris (Frontiers in Physiology, 2016)
The human embryonic kidney 293 (HEK-293) cells are commonly used as host for the heterologous expression of membrane proteins not least because they have a high transfection efficiency and faithfully translate and process proteins. In addition, their cell size, morphology and division rate, and low expression of native channels are traits that are particularly attractive for current-voltage measurements. Nevertheless, the heterologous expression of complex membrane proteins such as receptors and ion channels for biological characterization and in particular for single-cell applications such as electrophysiology remains a challenge. Expression of functional proteins depends largely on careful step-by-step optimization that includes the design of expression vectors with suitable identification tags, as well as the selection of transfection methods and detection parameters appropriate for the application. Here, we use the heterologous expression of a plant potassium, K+ channel, the Arabidopsis thaliana guard cell outward-rectifying K+ channel, AtGORK (At5G37500) in HEK-293 cells as an example, to evaluate commonly used transfection reagents and fluorescent detection methods, and provide a detailed methodology for optimized transient transfection and expression of membrane proteins for in vivo studies in general and for single-cell applications in particular. This optimized protocol will facilitate the physiological and cellular characterization of complex membrane proteins.